The Ideal of Female Beauty in Greek Tombstone Inscriptions and Writings of Early Christian Authors - Korečková, Andrea (The Biblical Annals, 2019)
The extant remains from both Classical and Hellenistic periods portray a body of a Greek woman in all its beauty. They do not cover what was once revealed. On the contrary, they bring the female beauty to the centre of attention. This freedom of expression gradually disappears and a body is exposed only when portraying a woman with colourful past to show her failures. This paper introduces Greek tombstone inscriptions that captured female beauty for the future generations. Upon this, a question arises: what do these inscriptions mean to a casual reader? What is their purpose? What value did a beautiful woman have in the ancient society? Was she somewhat different from those around her? How did emerging Christianity react to the Greek ideal of beauty? What ideas were adopted and what ideas were firmly rejected? These and many other questions have arisen during the study of the inscriptions that engage people even today.